Formasi Rohani Pemimpin Muda Berdasarkan 1 Timotius 4:6-16 dan Implementasinya bagi Pemimpin Muda Era Society 5.0 - Kharisda Mueleni Waruwu; Sugiono Sugiono; Fransius Kusmanto (Jurnal Teologi (JUTEOLOG), 2021)
Nowadays, there are not many churches who think about and prepare young Christian leaders in the era of society 5.0 who have spiritual provisions and good character to be able to become the next generation of the Church's future. Awakening the spiritual formation of young leaders in the era of society 5.0 is a good thing because it can provide innovation in Church leadership today. The purpose of this study is to provide an understanding and contribution of theological thinking from the study of 1 Timothy 4:6-16 regarding the spiritual formation of young leaders in the era of society 5.0. The approach used is to use a qualitative method with an exegesis approach to the spiritual formation of young leaders. From the results of the research of 1 Timothy 4:1-16, several principles of spiritual formation have been found that can be implemented for young leaders in the era of society 5.0, namely: rejecting the nature of the world and pursuing a pious life, always hoping for the living God, respecting oneself and being an example, always make the word as the center of life and ministry, not neglecting the responsibility as a servant.